Generation MTV a study on the influence of MTV and popular music on the values and identity of Filipino youth - Cruz, Ma. Patricia Chelo M. 1978-; Lacson, Jose R., Jr.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This research study aimed to investigate the extent of influence of popular music and MTV on the youth which are the primary audience. These two function not merely as communication mediums but teachers that inculcate values and identities of their young audience. The primary intention of this study is to underscore the role of Music Television or MTV in molding today's youth. Next is to compare the youth represented on MTV and Filipino youth in terms of lifestyle, priorities, beliefs and values. The study also aimed to scrutinize how popular music is used as a tool to communicate certain messages. Lastly, the study intended to compare selected Western and Asian content of videos and programs. The theory of George Gerbner, Cultivation Analysis claims that television, after heavy, constant and long-term exposure, will lead to a communal way of viewing the world for its audience. He calls this mainstreamed reality or altered reality based on what the television projects. Consequent to this is a change in values of the viewer. This is where the cultural erosion metaphor of Duane Varan steps in. According to him, Western television corrupts the viewers of other countries, thereby introducing new ideologies and values and eroding time-treasured traditions. The study adopted a purely qualitative approach using textual analysis of 38 music videos, observation of a few select MTV programs and focus interviews of the pertinent age group of young people. MTV's songs and programs epitomize a liberated and modern picture of youth, one notoriously called Generation X. This generation of youth are rebellious, irresponsible, reckless, devoid of goals. The Filipino counterpart, despite exposure to MTV has not drastically changed. Inevitably there have been significant changes but not enough to conclude that MTV should be banned altogether. In fairness, the channel has been exerting effort in producing local shows and projecting Asian culture as opposed to merely Western content. Thereby balancing the influx of messages and ideologies that its young audience are bound to embrace.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: MTV -- Philippines; Popular music -- Philippines; Music and youth